High-elasticity tpu / etpu composite monofilament and preparation process thereof
Patent Information
- Application Number
- CN202611296108.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-23
AI Technical Summary
本发明的目的包括:克服ETPU无法直接熔融纺丝的障碍,将其与TPU进行有效复合,制成连续、均匀的复合单丝;使复合单丝在保留TPU良好力学性能的同时,显著提高回弹性(目标回弹率≥60%)并降低密度(目标≤0.92g/cm3);解决两种材料因密度差异导致的共混不均和ETPU泡孔在加工过程中易破坏的问题;提供一种工艺解耦、设备改造成本低、易于工业化推广的制备方法
[0042]1.本发明采用对ETPU发泡微球进行低压气体浸渍预处理的技术手段,配合后续熔融共混及纺丝过程中温度与剪切应力的精确控制,使ETPU微球内部闭孔在加工全程中建立并维持与外部环境压力相匹配的气体背压,解决了ETPU因高温下内部气体膨胀导致泡孔破裂而无法直接熔融纺丝的技术难题,从而实现了ETPU微球在TPU基体中作为独立功能相完整保留(闭孔完整率≥92%),为复合材料提供了持久的轻量化与高回弹功能基础。通过气体浸渍预先在ETPU闭孔内充入高压CO2/N2,使泡孔内初始压力由常压(0.1MPa)提升至0.5~1.5MPa,当后续加工温度升至200℃时,泡孔内压力按Gay-Lussac定律同步升至1.6~4.8MPa,恰好与螺杆熔融段及喷丝孔入口处的熔体静压(约2~5MPa)相平衡,从而避免了因内外压差过大导致的泡孔壁屈曲失稳与破裂。这一压力预平衡策略从热力学根源上解决了发泡材料热加工的固有矛盾,无需对现有纺丝设备进行高压改造,具有极高的工程实用价值。
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer material processing technology, and in particular to a high-elasticity TPU / ETPU composite monofilament and its preparation process. Background Technology
[0002] Thermoplastic polyurethane (TPU) elastomers are a type of (AB)n-type block copolymer formed by the reaction of diisocyanates and polyols. Their molecular chains consist of alternating hard segments formed by chain extension of diphenylmethane diisocyanate (MDI) and 1,4-butanediol (BDO) and soft segments of polyether or polyester. Strong hydrogen bonding (NH···O=C) forms physical crosslinking points between the hard segments, imparting high modulus and heat resistance to the material. The soft segments exhibit an amorphous morphology with a glass transition temperature (Tg) as low as -50 to -30°C, providing the macromolecular chains with compliant movement. This microphase separation structure allows TPU to simultaneously possess excellent elastic recovery (30%–50% resilience), abrasion resistance, oil resistance, and low-temperature flexibility at room temperature, thus making it widely used in footwear, pipes, films, cable sheaths, and monofilaments. In the field of monofilaments, TPU monofilaments are commonly used in industrial screens, conveyor belt frames, fishing lines, medical sutures, and high-grade elastic fabrics.
[0003] Expanded thermoplastic polyurethane (ETPU) is a rapidly developing new type of lightweight functional material in recent years. Its preparation principle is as follows: TPU resin is impregnated in an autoclave under high temperature (130–160℃) and high pressure (10–30 MPa) conditions with a supercritical fluid (usually CO2 or N2), allowing gas molecules to fully dissolve in the TPU matrix. Subsequently, the pressure is rapidly released, utilizing thermodynamic instability to promote the homogeneous nucleation and growth of numerous bubbles within the matrix. Finally, water cooling is used for shaping, resulting in a material with a large number of independent closed-cell structures (pore size 20–150 μm, pore density 102). 6 ~10 9 pcs / cm 3 Expanded microspheres of ETPU. The density of ETPU can be as low as 0.15–0.40 g / cm³. 3 (Foaming ratio 5-15 times), rebound rate as high as 60%-70%, energy return efficiency of over 80%, and has been commercially applied on a large scale in high-end sports shoe midsoles (such as the Adidas Boost series).
[0004] ETPU microspheres are essentially closed-cell foam structures filled with high-pressure gas. When they are directly heated to above the melting point of TPU (typically ≥190℃) for melt spinning, the gas partial pressure inside the microspheres increases sharply with increasing temperature. According to the ideal gas law pV=nRT, when the temperature rises from room temperature (25℃) to 200℃, if the cell volume remains unchanged, the internal pressure will increase to approximately 1.59 times its original value. Furthermore, when the TPU matrix undergoes a viscoelastic transition above its melting point, its storage modulus increases from approximately 10... 6 Pa drops sharply to 10 3 ~10 4 Pa significantly weakens the creep resistance of the cell walls. When the internal gas pressure exceeds the surface tension limit of the cell walls, the cells undergo irreversible expansion and rupture. The ruptured gas escapes into the melt, forming macroscopic bubbles, which leads to severe unevenness in melt rheology during spinning, frequent fiber breakage, and even if it is managed to form fibers, the fibers are porous and spongy inside, with a mechanical strength less than 1 / 10 of that of pure TPU.
[0005] TPU resin (density 1.10~1.20g / cm³) 3 ) and ETPU microspheres (bulk density 0.15~0.35g / cm³) 3 The true density is approximately 0.30–0.55 g / cm³. 3 Significant density differences exist between ETPU and TPU. According to Stokes' law, with an ETPU particle size of 3 mm and a TPU melt viscosity of 500 Pa·s (190℃), the floating velocity is estimated to be approximately 0.05–0.15 mm / s. This means that significant segregation can occur within minutes during melt blending and static transport. Furthermore, TPU is a polar polymer; although the surface of ETPU is also made of TPU, the increased surface roughness after foaming reduces the actual effective contact area and weakens the interfacial bonding strength, resulting in low stress transfer efficiency in the composite material.
[0006] Currently, there are three main technical routes for the research and development of lightweight, high-elasticity fibers: First, using thermally expandable microcapsules blended with a thermoplastic matrix followed by spinning, achieving in-situ foaming during the spinning process. However, the foaming process is strongly coupled with the spinning and drawing process, making it difficult to simultaneously achieve the desired foaming ratio and fiber orientation. Second, using supercritical fluid foaming spinning technology, but this requires huge equipment investment and has an extremely narrow process window, making industrial-scale promotion difficult. Third, directly pulverizing ETPU particles into fine powder and then blending them with TPU for spinning. However, the pulverization process destroys the closed-cell structure of ETPU, causing it to lose its high resilience advantage. A long-standing technical bias in this field holds that the cell structure of ETPU is inevitably destroyed during melt processing, therefore ETPU can only be used for molding in the form of finished particles and cannot be used as a functional filler in spinning. This bias has led those skilled in the art to generally abandon the exploration of the ETPU / TPU blend spinning route. Summary of the Invention
[0007] To address the shortcomings of existing technologies, this invention provides a high-elasticity TPU / ETPU composite monofilament and its preparation process. The objectives of this invention include: overcoming the obstacle that ETPU cannot be directly melt-spun, effectively combining it with TPU to produce continuous and uniform composite monofilaments; and enabling the composite monofilaments to retain the good mechanical properties of TPU while significantly improving resilience (target resilience ≥60%) and reducing density (target ≤0.92 g / cm³). 3 This paper addresses the issues of uneven blending due to density differences between the two materials and the easy damage to ETPU foam cells during processing; it provides a preparation method that features process decoupling, low equipment modification costs, and ease of industrialization.
[0008] To achieve the above objectives, the present invention adopts the following technical solution:
[0009] A high-elasticity TPU / ETPU composite monofilament, by weight, comprises the following raw materials: 50-80 parts TPU resin, as the continuous matrix phase, providing mechanical strength and spinnability; 20-40 parts ETPU foamed microspheres, as the dispersed phase functional filler, providing high resilience and lightweight; 3-8 parts compatibility toughening agent, used to improve interfacial bonding and increase compatibility and toughness; 0.5-2 parts antioxidant, used to prevent thermo-oxidative degradation; 0.5-1.5 parts lubricant, used to improve processing fluidity and mold release properties; and 0.5-2 parts nucleating agent, used to regulate the crystallization of TPU soft segments and improve modulus.
[0010] Preferably, the TPU resin is a polyether-type or polyester-type thermoplastic polyurethane elastomer with a Shore A hardness of 85–95A. Polyether-type TPU has superior low-temperature resilience and hydrolysis resistance, making it suitable for sporting goods; polyester-type TPU has higher strength and abrasion resistance, making it suitable for industrial monofilaments. When the hardness is below 85A, the matrix modulus is too low, the initial modulus of the monofilament is insufficient, and it is prone to creep; when the hardness is above 95A, the processing temperature needs to be increased accordingly, which is not conducive to the protection of ETPU cell structure.
[0011] Preferably, the ETPU foamed microspheres are closed-cell expanded microspheres prepared by supercritical CO2 or N2 foaming with TPU as the matrix resin, having an average particle size of 2-5 mm and a bulk density of 0.15-0.35 g / cm³. 3 The foaming ratio is 5 to 15 times, and the closed-cell rate is not less than 92%. When the particle size is less than 2 mm, the specific surface area of the microspheres increases, and the number of interfaces with the TPU matrix increases. Although this is beneficial for dispersion, it also increases interface defects and reduces mechanical strength. When the particle size is greater than 5 mm, if the diameter of the monofilament is less than 1 mm, the diameter of a single ETPU microsphere exceeds 5 times the diameter of the monofilament. This makes it very easy to clog the spinneret orifice or cause breakage during spinning. The preferred particle size is 2 to 3 mm.
[0012] Preferably, the compatibility toughening agent is an ethylene-methyl acrylate-glycidyl methacrylate terpolymer (E-MA-GMA, brand name KG-108), wherein the GMA content is 6%–8%. The epoxy groups in the GMA groups can undergo ring-opening addition reactions with the hydroxyl or urethane groups at the ends of the TPU molecular chains at high temperatures, forming chemical bonds, thereby establishing a covalent bridge between the TPU matrix and the ETPU surface, significantly improving the interfacial adhesion strength. Furthermore, the E-MA copolymer segments have a low glass transition temperature (approximately -35°C), which also contributes to the toughening effect.
[0013] Preferably, the antioxidant is a mixture of hindered phenolic antioxidant 1010 and phosphite antioxidant 168 in a 1:1 mass ratio. 1010 provides the primary antioxidant effect by terminating the oxidation chain reaction by capturing peroxide free radicals; 168 provides the secondary antioxidant effect by decomposing hydrogen peroxide into a stabilizing product. The synergistic effect of the two is better than that of using either alone in terms of thermo-oxidative stabilization. The lubricant is either stearamide or pentaerythritol stearate. The former is an internal lubricant that can reduce the friction between TPU melt molecular chains and increase the melt index; the latter has both internal and external lubrication functions and low volatility at high temperatures, making it less likely to form carbon deposits at the spinneret. The nucleating agent is selected from nano talc powder (average particle size ≤100nm) or nano silica (average particle size ≤50nm). The nano nucleating agent provides heterogeneous nucleation sites during the cooling process of TPU melt, induces the formation of microcrystals in TPU soft segments, improves the initial modulus and creep resistance of monofilaments, and at the same time, the nanoparticles can be pinned at the TPU / ETPU interface to inhibit interfacial slip.
[0014] The present invention also proposes a preparation process for the aforementioned high-elasticity TPU / ETPU composite monofilament, which includes the following five steps.
[0015] Step S1: Low-pressure gas impregnation pretreatment of ETPU microspheres. First, load the ETPU foamed microspheres into a sealed impregnation vessel. After sealing, start the vacuum pump and evacuate the impregnation vessel to an absolute pressure of 5-15 kPa, maintaining this pressure for 30-60 minutes to remove the air originally present in the pores of the ETPU microspheres, as well as the moisture and volatile organic compounds adsorbed on the surface and in the pores of the microspheres. After vacuum degassing, inject a high-pressure gas medium into the impregnation vessel. The selected gas is industrial-grade nitrogen with a purity of not less than 99.5% or food-grade carbon dioxide with a purity of not less than 99.9%. The injection pressure is 0.5-1.5 MPa, the temperature is 40-60℃, and the holding time is 1.0-2.5 hours.
[0016] During this process, gas molecules diffuse and permeate from the open pores on the surface of ETPU microspheres into the closed pores, driven by both concentration and pressure gradients. According to Fick's second law, at 50°C, the diffusion coefficient of CO2 in TPU is approximately 2.5 × 10⁻⁶.-8 ~4.0×10 -8 cm 2 Within 2 hours, gas molecules can permeate through a cell wall thickness of approximately 50–80 μm, achieving sufficient exchange of gas components inside and outside the cells. After the pressure holding period, the pressure is slowly released to atmospheric pressure at a rate not exceeding 0.05 MPa / min to prevent cell wall rupture due to excessive pressure difference. Subsequently, the impregnated ETPU microspheres are discharged, sealed, and stored for later use.
[0017] The essence of this pretreatment step is to establish a certain gas back pressure in the closed pores inside the ETPU microspheres. During the subsequent melt blending and spinning process, when the ambient temperature rises to 190-205℃, the gas pressure inside the pores will increase from 0.5-1.5MPa at room temperature to about 1.6-4.8MPa. This pressure reaches a dynamic balance with the external pressure (about 2-5MPa) applied to the ETPU surface by the molten TPU matrix, thereby effectively avoiding the expansion and rupture of the pore walls due to excessive internal and external pressure difference in the thermally softened state.
[0018] Step S2: Low-temperature mechanical premixing. Accurately weigh the ETPU microspheres treated in Step S1, along with TPU resin, compatibility toughening agent, antioxidant, lubricant, and nucleating agent according to the preset ratio, and then add them to a high-speed mixer. Cooling water is circulated through the mixer jacket to control the mixing temperature to not exceed 50℃. The stirring speed is 100–300 rpm, and the mixing time is 10–25 minutes, until all components are macroscopically uniformly distributed, thus obtaining the premix.
[0019] The key to this step is to control the mixing temperature to no more than 50°C to prevent the TPU layer on the surface of the ETPU microspheres from becoming sticky and agglomerating; at the same time, low-speed stirring can avoid the ETPU cell walls from breaking due to violent impact.
[0020] Step S3: Special screw extrusion melt blending and granulation. The premix obtained in step S2 is fed into a co-rotating twin-screw extruder at a constant rate through a loss-in-weight metering feeder for melt blending, devolatilization, extrusion, cooling, and pelletizing to obtain composite masterbatch. The co-rotating twin-screw extruder used has a screw diameter of 75 mm and a length-to-diameter ratio of 44:1 to 52:1.
[0021] The screw components, from the feed port to the die head, are arranged as follows:
[0022] The conveying section (0~8L / D) uses large-lead threaded elements (lead 64mm) for the rapid conveying and compression of solid materials;
[0023] The melting section (8-18L / D) uses a small-lead threaded element (40mm lead) in conjunction with a meshing block with a 45° staggered angle for melting and plasticizing the TPU matrix;
[0024] The compression section (18-28 L / D) uses medium-lead threaded elements (48 mm lead) in conjunction with toothed disk elements for further homogenization and compression of the melt;
[0025] The mixing section (28-38 L / D) employs a combination of toothed discs and reverse threaded elements. The toothed discs provide distributed mixing, ensuring that the ETPU microspheres are uniformly dispersed in the TPU melt without being broken. The reverse threaded elements increase the residence time of the melt in the mixing section (extending it by approximately 30%-50%), promoting the interfacial wetting and chemical coupling reaction between the ETPU microsphere surface and the TPU matrix. The shear stress generated by its reverse conveying action is controlled to not exceed 30 kPa, which is lower than the critical rupture stress of the ETPU cell wall (approximately 45 kPa).
[0026] The exhaust section (38-44 L / D) is connected to the vacuum degassing system to remove water vapor and trace amounts of low-molecular-weight volatiles generated by the thermal decomposition of TPU from the melt; the homogenization section (44-52 L / D) uses small-lead threaded elements (32 mm lead) to stabilize melt pressure and flow rate, ensuring the uniformity of the extruded strip diameter.
[0027] Preferably, the extrusion temperatures from the feed port to the die head are as follows: Zone 1 135-145℃, Zone 2 155-165℃, Zone 3 170-180℃, Zone 4 175-185℃, Zone 5 180-190℃, Zone 6 185-195℃, Zone 7 190-200℃, and Zone 8 (die head) 195-205℃. This design features gradual heating with peak temperatures later in the process, preventing the ETPU microspheres from expanding and rupturing due to instantaneous high temperatures before entering the melting zone. The maximum processing temperature (205℃) is 15-35℃ lower than the conventional TPU modification granulation temperature (usually 220-240℃).
[0028] Preferably, the screw speed is 200–350 rpm. The low speed combined with the large length-to-diameter ratio screw ensures that the material achieves sufficient mixing effect while minimizing the frictional heat generated by mechanical shearing. A vacuum pump is connected to the exhaust section to maintain an absolute pressure of 20–40 kPa (i.e., a vacuum degree of -0.06 to -0.08 MPa). This vacuum degree setting is significantly lower than that of conventional devolatilization processes to avoid the loss of back pressure due to accelerated diffusion and escape of gas inside the ETPU microspheres caused by excessively high vacuum. The extrudate is cooled to room temperature in a 6–10 m long water bath cooling tank (water temperature 25–35 °C). After the surface moisture is dried by air knife, it enters a pelletizer (speed 800–1200 rpm) to be cut into cylindrical composite masterbatches with a length of 3–5 mm. The masterbatches are dried in a drying oven at 60–80 °C for 6–10 hours to reduce the moisture content to no more than 0.03 wt%, and then sealed and packaged for later use.
[0029] Step S4: Melt spinning of composite monofilaments. The composite masterbatch obtained in step S3 is further dried (80℃×6h, vacuum drying, vacuum degree -0.09MPa) and then fed into a single-screw extruder. The melt flow rate is precisely controlled by a metering pump, and the melt is extruded through the spinning box and spinneret to form a fine melt stream. After cooling, oiling, drawing, heat setting, and winding, composite monofilaments are obtained. The single-screw extruder used has a screw diameter of 45mm, a length-to-diameter ratio of 28:1, and a compression ratio of 3:1.
[0030] Preferably, the spinning temperature from the feeding section to the die head is as follows: Zone 1 160-165℃, Zone 2 175-180℃, Zone 3 190-195℃, Zone 4 195-200℃, and Die head 195-205℃, which is 15-25℃ lower than that of pure TPU spinning (usually 210-230℃).
[0031] Preferably, the spinneret has 30–120 holes with a diameter of 0.3–1.2 mm and an aspect ratio of 2–4. The holes are circular, and the inlet angle is 60° to reduce tensile stress concentration of the melt at the inlet. The metering pump operates at 5–20 rpm, with a single-hole output of 0.5–5.0 g / min, calculated based on the target monofilament diameter and winding speed. The melt stream extruded from the spinneret passes through an air gap of 10–30 mm (air temperature 25–35°C, relative humidity not exceeding 60%) before entering a cooling water bath or cooling air box (wind speed 0.5–2.0 m / s) at a temperature of 15–30°C for cooling and solidification. The cooling water bath is 1.5–3.0 m long, and the water temperature uniformity is controlled within ±1°C. After cooling, the nascent filaments are oiled by an oiling roller. The spinning oil is a mineral oil-based emulsion containing antistatic agents and sizing agents, with a solid content of 15% to 25% and an oiling rate of 0.8% to 1.5%.
[0032] Preferably, the drawing and heat setting process employs a single-stage heat drawing followed by a two-stage heat setting. The first-stage drawing uses a twin-roller drawing machine with a draw ratio of 3.5–6.5 times. The drawing medium is a circulating water bath or hot rollers, and the temperature in the drawing zone is 50–80°C. Within this temperature range, TPU is in a highly elastic state (above Tg but below the viscous flow temperature), allowing macromolecular chain segments to align along the direction of external force. The hydrogen bond physical crosslinking points of the hard segments rearrange with the slippage of the molecular chains, forming a preferred orientation structure along the fiber axis. The second-stage heat setting uses a 250mm diameter hot roller with a hard chrome-plated surface to heat-set the drawn filament bundle at 100–130°C. The heat setting ratio (relaxation ratio) is set to 0.95–1.0 times to eliminate internal stress generated during drawing and stabilize the resilience of the monofilament. After heat setting, the filament bundle passes through a guide disc and a tension controller, and is finally wound into a cylinder on a winding head. The winding speed is 200-600 m / min, and the winding tension is controlled within the range of 0.5-1.5 cN / dtex.
[0033] Step S5: Post-processing and shaping. The composite monofilament bobbin obtained in step S4 is placed in a constant temperature and humidity oven and heat-treated at 80-110℃ for 2-6 hours. Then, it is slowly cooled to room temperature at a rate of 0.5-1.0℃ / min. After removal, it is placed in a standard environment (temperature 23±2℃, relative humidity 50%±5%) for more than 48 hours to obtain the final product.
[0034] The essence of post-treatment and shaping lies in promoting more thorough microphase separation between the hard and soft segments in the TPU matrix. Through heat treatment at 80–110℃ (a temperature higher than the hard segment's Tg but lower than its melting temperature Tm by approximately 140–180℃), sufficient mobility is granted to the hard segment chains, allowing them to recombine through hydrogen bonds to form a more complete physical cross-linked network. Simultaneously, the hard segments originally dispersed in the soft segments are repelled, thus improving the degree of microphase separation. Differential scanning calorimetry (DSC) measurements show that the melting enthalpy of the hard segment phase region in the post-treated TPU matrix increases by approximately 15%–25%, indicating improved hard segment order. Slow cooling prevents thermal stress caused by sudden cooling, ensuring batch-to-batch stability of monofilament performance.
[0035] In the composite monofilament prepared by this invention, TPU serves as the continuous phase matrix, and ETPU microspheres, as the dispersed phase functional filler, are uniformly distributed within the matrix. The ETPU microspheres are arranged in a beaded pattern along the monofilament axis, with their long axis aligned with the monofilament axis, and an aspect ratio of approximately 1:1.5 to 1:4.0, depending on the draw ratio. Each ETPU microsphere maintains a complete closed-cell structure, with a closed-cell integrity rate of not less than 92%, an average pore diameter of 20–80 μm, and a pore wall thickness of 2–10 μm.
[0036] The mechanism of the rebound synergistic enhancement of the composite monofilament is as follows: When an external force is applied to the composite monofilament, its energy dissipation and rebound process can be divided into three stages.
[0037] In the initial loading stage (strain less than 50%), the external force is transmitted to the ETPU microspheres through the TPU continuous phase matrix. The soft segment molecular chains of the TPU matrix undergo conformational changes under the action of the external force, transforming from random coils to extended chains and storing entropy elasticity. At the same time, the closed-pore gas inside the ETPU microspheres is compressed, the gas volume decreases and the pressure increases. According to Boyle's law, during the compression process, the gas absorbs part of the work done by the external force and converts it into pressure potential energy for storage.
[0038] During the later stages of loading (strain 50%–200%), as strain increases, the hard segment hydrogen bond physical crosslinking points in the TPU matrix begin to dissociate, and the macromolecular chains undergo relative slippage, resulting in irreversible plastic deformation. At this time, the gas compression inside the ETPU microspheres has reached a high pressure, generating an outward expansion thrust on the cell walls, which macroscopically manifests as a stretching force on the TPU matrix, offsetting part of the matrix softening effect caused by the decrosslinking of hard segments.
[0039] During the unloading and rebound phase, after the external force is removed, the undamaged hard segment physical cross-linking points in the TPU matrix recover rapidly (response time less than 0.1 seconds), providing initial rapid rebound and recovering approximately 60%–70% of the deformation. Subsequently, the compressed gas inside the ETPU microspheres begins to expand and do work, releasing the stored pressure potential energy and pushing the cell walls outward to restore their original shape, further recovering approximately 15%–25% of the remaining deformation. The synergistic effect of these two processes results in a total resilience rate of over 65% for the composite monofilament, significantly higher than the theoretical estimate (approximately 50%) of the linear sum of the two components.
[0040] Regarding the density reduction mechanism, the closed-cell structure of ETPU microspheres results in an effective density of only 0.30–0.50 g / cm³. 3 It is far lower than the 1.15 g / cm³ of the TPU matrix. 3 When ETPU is dispersed in the matrix at a ratio of 20–40 parts, the overall density of the composite monofilament, weighted by volume fraction, can be increased from 1.15 g / cm³. 3 Reduced to 0.78–0.92 g / cm³ 3 The weight loss ranges from 20% to 32%.
[0041] Compared with the prior art, the beneficial effects of the present invention are:
[0042] 1. This invention employs a low-pressure gas impregnation pretreatment technique for ETPU foamed microspheres, combined with precise control of temperature and shear stress during subsequent melt blending and spinning processes. This allows the closed pores inside the ETPU microspheres to establish and maintain a gas back pressure that matches the external environmental pressure throughout the entire processing. This solves the technical problem that ETPU cannot be directly melt-spun due to the rupture of the pores caused by the expansion of internal gas at high temperatures. As a result, the ETPU microspheres are completely preserved as an independent functional phase in the TPU matrix (closed pore integrity rate ≥92%), providing a durable foundation for lightweight and high resilience in composite materials. By pre-filling the closed-cell ETPU with high-pressure CO2 / N2 through gas impregnation, the initial pressure inside the cells is increased from atmospheric pressure (0.1 MPa) to 0.5–1.5 MPa. When the subsequent processing temperature rises to 200°C, the pressure inside the cells rises synchronously to 1.6–4.8 MPa according to the Gay-Lussac law, which precisely balances the static pressure of the melt at the screw melting section and the spinneret inlet (approximately 2–5 MPa). This avoids buckling instability and rupture of the cell walls caused by excessive internal and external pressure differences. This pressure pre-balancing strategy solves the inherent contradictions in the thermal processing of foamed materials from a thermodynamic perspective, without requiring high-pressure modifications to existing spinning equipment, and has extremely high engineering practical value.
[0043] 2. This invention constructs a composite structure of a continuous TPU matrix and dispersed ETPU microspheres, combined with a chemical bonding layer formed at the interface by a compatibility toughening agent. This allows the composite monofilament to simultaneously utilize two rebound mechanisms under stress: the entropic elastic recoil of the TPU matrix and the expansion and energy release of compressed gas within the ETPU pores. Furthermore, these two mechanisms form a rapid-delay cascade synergy over time, ultimately achieving a rebound rate (62%–72%) far exceeding the expectations of single components and linear superposition. This represents an improvement of 48%–71% compared to pure TPU monofilaments and 24%–44% compared to the theoretical linear superposition value (approximately 50%), demonstrating significant synergistic effects. During the loading phase, the external force is absorbed sequentially by the entropy change in the molecular chain conformation of the TPU matrix and the volume compression of the gas within the ETPU pores, stored in the form of entropy elasticity and pressure potential energy. During the unloading phase, the TPU matrix first rapidly retracts (response time less than 0.1 seconds), recovering approximately 60%–70% of its deformation. Subsequently, the compressed gas within the ETPU pores slowly expands and releases energy (response time approximately 0.1–0.5 seconds), driving the pore walls to recover, additionally recovering approximately 15%–25% of the deformation. This staggered synergy between the two phases over time effectively compensates for the inherent deficiency of insufficient rebound driving force in the later stages of deformation caused by a single TPU matrix.
[0044] 3. This invention uses ETPU microspheres as a lightweight functional filler. By utilizing the non-effective volume occupied by their internal closed-cell structure, the overall density of the composite monofilament is reduced from 1.15 g / cm³ of pure TPU. 3 Reduced to 0.78–0.92 g / cm³ 3The weight reduction ranges from 20% to 32%, and the density reduction shows a good linear relationship with the amount of ETPU added. This indicates that the ETPU cell structure is preserved intact throughout the processing, without significant collapse or TPU matrix penetration into the cell interior. Thus, while achieving lightweighting, mechanical properties are not degraded.
[0045] 4. This invention controls the melt blending temperature at 135–205°C and the spinning temperature at 160–205°C, which is 15–35°C lower than the conventional TPU processing temperature. Combined with the low-shear design of the screw mixing section toothed disc + reverse thread element (shear stress ≤30kPa, lower than the critical rupture stress of ETPU cell wall 45kPa), and the low-pressure control of the vacuum exhaust section (absolute pressure 20–40kPa, to avoid excessive extraction of gas from inside ETPU), this invention comprehensively protects the ETPU cell structure from three dimensions: temperature field, stress field, and atmosphere field. This ensures that the cell integrity is maintained at over 92%, which is far higher than the 50%–70% of conventional high-temperature processing.
[0046] 5. This invention employs a gentle processing route encompassing low-temperature mechanical premixing → low-temperature weak-shear melt blending and granulation → low-temperature gradient drawing and spinning → relaxation heat setting → slow cooling post-treatment, effectively solving the problem of density differences (Δρ≈0.6~0.9g / cm³) between TPU and ETPU. 3 This addresses the melt blending delamination problem caused by [unclear - possibly a specific problem or issue]. Simultaneously, by optimizing the draw ratio (3.5–6.5 times) and heat setting temperature (100–130℃), an optimal balance between molecular chain orientation and hard segment microphase separation is achieved. This results in composite monofilaments possessing both high strength (2.8–4.2 cN / dtex) and high elasticity (62%–72% resilience), overcoming the technical contradiction of traditional elastic monofilaments where strength and elasticity cannot be simultaneously achieved.
[0047] 6. The preparation process provided by this invention is compatible with existing general melt spinning production lines. It does not require the addition of ultra-high pressure equipment or special spinning components. It only requires the addition of a low-pressure gas impregnation kettle and corresponding temperature control modifications. The equipment investment increases by no more than 15% of the existing production line. Moreover, the process has a wide operating window (it can maintain stable performance within a temperature fluctuation of ±5℃ and a pressure fluctuation of ±0.2MPa), and has good prospects for industrialization and cost competitiveness. Detailed Implementation
[0048] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with existing known technologies. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0049] The following tests used the following basic raw material specifications:
[0050] The TPU resin used is a polyether-type thermoplastic polyurethane elastomer with a Shore A hardness of 85A and a melt flow index (190℃ / 2.16kg) of 15–25 g / 10 min, designated BASF Elastollan® 1185A. The ETPU foamed microspheres are closed-cell expanded microspheres prepared by supercritical CO2 foaming of TPU as the matrix resin, with an average particle size of 3 mm, a foaming ratio of 10, and a bulk density of 0.30 g / cm³. 3 The closed-cell rate is no less than 92%, and a general-purpose product from a domestic ETPU manufacturer is selected. The compatibility toughening agent is ethylene-methyl acrylate-glycidyl methacrylate terpolymer (E-MA-GMA), with a GMA content of 7%, brand name KG-108, manufactured by Sumitomo Chemicals, Japan. The antioxidant is a 1:1 mass ratio blend of hindered phenolic antioxidant 1010 and phosphite antioxidant 168. The lubricant is stearamide (industrial grade, purity no less than 98%). The nucleating agent is nano-talc powder with an average particle size of 80nm.
[0051] Example 1. Preparation of highly elastic TPU / ETPU composite monofilament:
[0052] A high-elasticity TPU / ETPU composite monofilament, the raw material formula by weight is as follows: 65 parts TPU resin, 30 parts ETPU foamed microspheres, 5 parts compatibility toughening agent KG-108, 0.5 parts antioxidant 1010, 0.5 parts antioxidant 168, 1.0 part lubricant (stearamide), 1.0 part nucleating agent (nano talc), totaling 103 parts.
[0053] Its preparation process is as follows:
[0054] Step S1: Load ETPU foamed microspheres into a sealed impregnation vessel, evacuate to an absolute pressure of 10 kPa, and maintain for 45 minutes. After vacuum degassing, inject CO2 gas into the impregnation vessel to a pressure of 1.0 MPa, maintain the pressure at 50°C for 1.5 hours, and then slowly depressurize to atmospheric pressure at a rate not exceeding 0.05 MPa / min. Discharge and seal for later use.
[0055] Step S2: After accurately weighing the ETPU microspheres treated in step S1 with TPU resin, KG-108, antioxidant 1010, antioxidant 168, stearamide and nano talc powder according to the specified ratio, put them into a high-speed mixer. Cooling water is circulated in the jacket of the mixer to control the temperature to not exceed 50°C. The stirring speed is 200 rpm and the mixing time is 15 minutes to obtain the premix.
[0056] Step S3: The premixed material is fed into a co-rotating twin-screw extruder through a loss-in-weight metering feeder. The screw diameter is 75 mm and the length-to-diameter ratio is 48:1. The screw element combination is as follows: conveying section (0-8 L / D, lead 64 mm), melting section (8-18 L / D, lead 40 mm, with 45° staggered meshing blocks), compression section (18-28 L / D, lead 48 mm, with toothed discs), mixing section (28-38 L / D, toothed discs + reverse screw elements, shear stress ≤30 kPa), degassing section (38-44 L / D, vacuum degassing), and homogenization section (44-52 L / D, lead 32 mm). The extrusion temperatures from the feed port to the die head are as follows: Zone 1 140℃, Zone 2 160℃, Zone 3 175℃, Zone 4 180℃, Zone 5 185℃, Zone 6 190℃, Zone 7 195℃, and Zone 8 (die head) 200℃. The screw speed is 280 rpm, and the absolute pressure in the exhaust section is maintained at 30 kPa. The extrudate is cooled to room temperature in an 8m long water bath cooling tank (water temperature 30℃), dried by an air knife, and then fed into a pelletizer (speed 1000 rpm) to be cut into cylindrical composite masterbatches with a length of 3-5mm. The masterbatches are then dried in a 70℃ drying oven for 8 hours to reduce the moisture content to no more than 0.03wt%, and then sealed and packaged for later use.
[0057] Step S4: After further drying (80℃×6h, vacuum drying, vacuum degree -0.09MPa), the composite masterbatch is fed into a single-screw spinning extruder with a screw diameter of 45mm, an aspect ratio of 28:1, and a compression ratio of 3:1. The spinning temperatures from the feed section to the die head are as follows: Zone 1 162℃, Zone 2 178℃, Zone 3 192℃, Zone 4 198℃, and Die head 200℃. The spinneret has 60 holes with a diameter of 0.6mm, an aspect ratio of 3, and an inlet angle of 60°. The metering pump speed is 10rpm. The melt stream passes through a 20mm air gap and then enters a 25℃ cooling water bath (2.0m in length, water temperature uniformity ±1℃) for cooling and solidification. The cooled nascent filaments are then oiled by an oil roller. The oil is a mineral oil-based emulsion containing antistatic agents and slugging agents, with a solid content of 20% and an oiling rate of 1.0%. The primary heat drawing uses a twin-roller drawing machine with a draw ratio of 5.0 and a drawing temperature of 70℃ (water bath). The secondary heat setting uses hot rollers with a heat setting temperature of 120℃ and a heat setting ratio of 0.98. The winding speed is 400m / min, and the winding tension is controlled at 1.0cN / dtex.
[0058] Step S5: Place the wound composite monofilament bobbin in a constant temperature and humidity oven and heat treat it at 90℃ for 3 hours. Then, slowly cool it to room temperature at a rate of 0.8℃ / min. After taking it out, place it in a standard environment (temperature 23±2℃, relative humidity 50%±5%) for more than 48 hours to obtain the final product.
[0059] Example 2: The only difference from Example 1 is the raw material formulation and some process parameters. Specifically, it contains 60 parts TPU resin, 35 parts ETPU foamed microspheres (the upper limit of ETPU content), 5 parts KG-108, and the remaining additives are the same as in Example 1, totaling 103 parts. In the process parameters: the maximum temperature in S3 is 200℃, the draw ratio in S4 is 5.5 times (the upper limit of draw ratio), and the winding speed in S4 is 440m / min. The remaining process steps and parameters are the same as in Example 1.
[0060] Example 3: The only difference from Example 1 is the raw material formulation and some process parameters. Specifically, it contains 70 parts TPU resin, 25 parts ETPU foamed microspheres (at the lower limit of ETPU content), 5 parts KG-108, and the remaining additives are the same as in Example 1, totaling 103 parts. The process parameters are: S1 impregnation pressure is 0.8 MPa (at the lower limit of impregnation pressure), S4 draw ratio is 4.5 times, and S4 winding speed is 360 m / min. The remaining process steps and parameters are the same as in Example 1.
[0061] Example 4: The only difference from Example 1 is that some process parameters are different. Specifically, the S1 impregnation pressure is 1.2 MPa (the upper limit of the impregnation pressure), and the other raw material formulas and process parameters are the same as in Example 1.
[0062] Examples 1-4 constitute an orthogonal experimental sequence to investigate the influence of three core variables (ETPU content, gas impregnation pressure, and draw ratio) on product performance at different levels, covering the boundary values of the three key parameters. Specifically, Example 1 represents the optimal formulation (ETPU content 30 parts, impregnation pressure 1.0 MPa, draw ratio 5.0 times); Example 2 examines the upper boundary of ETPU content (35 parts) and the upper boundary of draw ratio (5.5 times); Example 3 examines the lower boundary of ETPU content (25 parts) and the lower boundary of impregnation pressure (0.8 MPa); and Example 4 examines the upper boundary of impregnation pressure (1.2 MPa).
[0063] Example 5: The only difference from Example 1 is that the amount of compatibility toughening agent KG-108 in the raw material formulation is 3 parts (lower limit of protection), totaling 101 parts. The other raw material formulations and process parameters are the same as in Example 1.
[0064] Example 6: The only difference from Example 1 is that the amount of compatibility toughening agent KG-108 in the raw material formula is 8 parts (upper limit of protection range), totaling 106 parts. The other raw material formulas and process parameters are the same as in Example 1.
[0065] Example 7: The only difference from Example 1 is that the heat setting temperature of S4 is 100℃ (lower limit of protection range) in the process parameters. The other raw material formulas and process parameters are the same as in Example 1.
[0066] Example 8: The only difference from Example 1 is that the maximum temperature of S4 spinning is 205℃ (upper limit of the protection range) in the process parameters. The other raw material formulas and process parameters are the same as in Example 1.
[0067] Examples 5-8 constitute a single-factor series validation, which respectively investigated the effects of the amount of compatible toughening agent (3 parts, 8 parts), heat setting temperature (100℃, 130℃), and spinning temperature (205℃) on performance, covering the upper and lower limits of each independent parameter in the formulation and process.
[0068] Comparative Example 1: The difference from Example 1 is that the gas impregnation pretreatment is not performed in step S1 (i.e., step S1 is cancelled, and the ETPU microspheres are used directly as is), and the other raw material formulations and process parameters are the same as in Example 1.
[0069] Comparative Example 2: The difference from Example 1 is that the maximum temperature in step S3 is increased to 220°C and the maximum temperature in step S4 spinning is increased to 215°C (the conventional TPU processing temperature). The remaining raw material formulation and process parameters are the same as in Example 1 (including S1 gas impregnation pretreatment).
[0070] Comparative Example 3: The difference from Example 1 is that the compatibility toughening agent KG-108 (0 parts) is not added to the raw material formula, the TPU resin is adjusted to 70 parts to maintain the total number of parts, and the other raw material formulas and process parameters are the same as in Example 1.
[0071] Comparative Example 4: Pure TPU monofilament, with the following raw material formulation: 100 parts TPU resin, 0.5 parts antioxidant 1010, 0.5 parts antioxidant 168, 1.0 part lubricant, and 1.0 part nucleating agent, excluding ETPU microspheres and toughening agents, totaling 103 parts. The preparation process adopted conventional TPU spinning technology: after drying, it was directly fed into a single-screw spinning extruder. The spinning temperatures from the feed section to the die head were as follows: Zone 1 170℃, Zone 2 190℃, Zone 3 210℃, Zone 4 215℃, and Die Head 210℃. The draw ratio was 5.0, the draw temperature was 70℃, the heat setting temperature was 120℃, and the winding speed was 400m / min. The remaining post-treatment was the same as in Example 1.
[0072] Comparative Example 5: The difference from Example 1 is that the impregnation pressure in step S1 is 0.2 MPa (lower than the lower limit of the protection range of 0.5 MPa), and the other raw material formulations and process parameters are the same as in Example 1.
[0073] Comparative Example 6: The difference from Example 1 is that the draw ratio in step S4 is 7.5 times (higher than the upper limit of the protection range of 6.5 times), the winding speed in S4 is adjusted to 600m / min accordingly, and the other raw material formulas and process parameters are the same as in Example 1.
[0074] Comparative Examples 1-4 constitute the core innovation comparative tests, verifying the performance differences under four benchmark conditions: no gas impregnation pretreatment, conventional high-temperature processing (220℃), no compatibility toughening agent, and pure TPU monofilament. Comparative Examples 5-6 constitute parameter deviation boundary verification tests, examining two extreme deviations beyond the scope of this invention: excessively low impregnation pressure (0.2MPa) and excessively high draw ratio (7.5 times), to clarify the boundary conditions of the process window. Unless otherwise specified, the basic raw material specifications remained consistent in all tests. The performance testing methods were standardized to ensure data comparability.
[0075] All composite monofilaments prepared in the examples and comparative examples were equilibrated in a standard environment (temperature 23±2℃, relative humidity 50%±5%) for 48 hours before performance testing. The standards, conditions, and descriptions for each test item are as follows:
[0076] The rebound rate was tested according to ASTM D2632 standard using a falling ball rebound tester with a steel ball diameter of 16mm and a drop height of 500mm. The steel ball was allowed to fall freely and impact the specimen, and the rebound height H was recorded. The rebound rate was calculated as H / 500 × 100%. Each specimen was tested 5 times, and the average value was taken. The specimen thickness was not less than 10mm (prepared by multi-layer winding of monofilament).
[0077] Density was tested according to ASTM D792 standard, using an analytical balance (accuracy 0.0001g) with a density measuring kit, and the water displacement method was employed. The impregnation solution was distilled water, and the temperature was 23℃. The sample mass was not less than 1.0g, and the average value was taken from three tests.
[0078] Breaking strength and elongation at break were tested according to ASTM D3822 standard using a single-yarn tensile testing machine with a clamping distance of 250 mm, a stretching speed of 250 mm / min, and a pretension of 0.05 cN / dtex. Twenty monofilaments were tested for each sample, and the average value was taken to calculate the breaking strength (in cN / dtex) and elongation at break (%).
[0079] The diameter of a single filament was determined using a microscopic projection method with a projector (accuracy 0.001 mm). Three cross-sectional positions were tested for each single filament, and a total of 20 single filaments were tested. The average diameter and the coefficient of variation (CV) of the diameter were calculated.
[0080] Melt flow index (MFI) is tested according to ASTM D1238 standard, with test conditions of 190℃ / 2.16kg, unit g / 10min, and is used to evaluate processing fluidity.
[0081] Cell structure observation was performed using scanning electron microscopy (optical microscope). After liquid nitrogen fracturing, the samples were sputter-coated with gold, and an accelerating voltage of 5kV was applied. The morphology and integrity of ETPU cells on the cross-section and longitudinal section were observed. The cell integrity rate was determined by statistically analyzing the percentage of intact cells out of the total number of cells using image analysis software.
[0082] The spinning breakage rate is a statistic that measures the average number of yarn breaks per hour during continuous spinning, used to assess spinnability.
[0083] The overall performance data of each embodiment is listed in Table 1, and the overall performance data of each comparative example is listed in Table 2.
[0084] Table 1. Overall performance data of Examples 1-8
[0085] Rebound rate (%) 68 70 65 69 63 64 65 66 <![CDATA[Density (g / cm 3 )]]> 0.85 0.8 0.9 0.84 0.86 0.84 0.86 0.86 Fracture strength (cN / dtex) 3.5 3 3.8 3.3 3.8 3.1 3.4 3.2 Elongation at break (%) 420 360 470 400 440 390 430 450 Single filament diameter (mm) 0.32 0.28 0.36 0.32 0.33 0.31 0.33 0.34 Diameter CV value (%) 2.5 3 2.4 2.8 2.7 2.9 2.6 3 MFI (g / 10min) 11.5 13.8 9.8 12 16.3 8.5 11.8 13.5 Cell integrity rate (%) 95 92 96 94 94 93 95 93 Decapitation rate (times / hour) ≤1 ≤1 ≤1 ≤1 ≤1 ≤1 ≤1 ≤1
[0086] Table 2. Overall performance data of Comparative Examples 1–6
[0087] Rebound rate (%) 43 55 51 42 47 55 <![CDATA[Density (g / cm 3 )]]> 1.02 0.87 0.87 1.15 0.98 0.84 Fracture strength (cN / dtex) 1.8 3.2 2.5 3.2 1.9 3.7 Elongation at break (%) 280 390 350 510 300 340 Single filament diameter (mm) 0.38 0.33 0.34 0.32 0.36 0.28 Diameter CV value (%) 8.5 4.2 4.8 2.2 6.8 4 MFI (g / 10min) 8.5 14.6 18.5 12 7.8 12.5 Cell integrity rate (%) 0 65 94 — 15 92 Decapitation rate (times / hour) >15 6 4 2 >12 2
[0088] Data Analysis:
[0089] 1. Effect of ETPU content on density and resilience. A comparison of Example 3 (25 parts ETPU), Example 1 (30 parts ETPU), and Example 2 (35 parts ETPU) shows that the density increases from 0.90 g / cm³. 3 Reduced to 0.85 g / cm³ 3 Further reduced to 0.80 g / cm³ 3 The downward trend is consistent with the theoretical expectations of the composite material mixing principle. For every 5 parts increase in ETPU content, the density decreases by approximately 0.05–0.06 g / cm³. 3 This indicates that the ETPU cell structure remained intact during processing, and no significant infiltration of the TPU matrix into the cell interior occurred. If cell collapse had occurred, the effective density of the ETPU would have been close to that of the TPU matrix (approximately 1.15 g / cm³). 3 The rate of density decrease will be significantly reduced. The resilience increases monotonically with increasing ETPU content, from 65% (25 parts) to 68% (30 parts) and then to 70% (35 parts), but the marginal gain decreases. When the ETPU content exceeds 30 parts, the average spacing between microspheres decreases from about 3.2 times the particle size to about 2.1 times the particle size. During the stretching process, the thickness of the TPU matrix bridging layer between adjacent ETPU microspheres is reduced to less than 50 μm. This thin layer becomes a stress concentration area during the stretching-retraction cycle, and the formation of some microcracks increases viscous loss. Therefore, 30 parts is the balance point with better overall performance.
[0090] 2. Effect of Impregnation Pressure on Cell Integrity. A comparison of Examples 3 (0.8 MPa), 1 (1.0 MPa), and 4 (1.2 MPa) shows that when the impregnation pressure increases from 0.8 MPa to 1.2 MPa, the resilience increases from 65% to 69%, but the breaking strength decreases from 3.8 cN / dtex to 3.3 cN / dtex. Thermodynamic analysis indicates that when the impregnation pressure is 0.8 MPa, the pressure of the gas inside the cell at 200°C is p2 = 0.8 × 473 / 298 = 1.27 MPa; the external melt static pressure is approximately 2–5 MPa, and the tensile stress σ on the cell wall… h =(p ext -p gas Substituting r = 50 μm, t = 3 μm, p ext Take the median value of 3MPa, σ h =(3-1.27)×50 / (2×3)=14.4MPa, which is close to the creep strength limit of TPU at 200℃ (approximately 12-15MPa), indicating that the foam wall is in a critical stable state. When the impregnation pressure increases to 1.2MPa, p2=1.91MPa, σ h =(3-1.91)×50 / (2×3)=9.1MPa, the safety margin is increased, and the resilience rate increases accordingly. However, higher impregnation pressure means that the bubble wall has been pre-stretched at room temperature (the internal pressure increases from 0.8 to 1.2MPa, increasing the initial tensile stress on the bubble wall by about 50%), making the bubble wall more prone to failure during subsequent spinning and drawing processes, thus reducing the breaking strength. The optimal impregnation pressure window is 0.8~1.2MPa.
[0091] 3. Effect of draw ratio on orientation degree and resilience. A comparison of Example 3 (4.5 times), Example 1 (5.0 times), and Example 2 (5.5 times) shows that the breaking strength decreased from 3.8 cN / dtex to 3.5 cN / dtex and then to 3.0 cN / dtex, while the resilience increased from 65% to 68% and then to 70%. When the draw ratio increased from 4.5 times to 5.5 times, the orientation degree of the TPU molecular chains increased (orientation degree f≈1-λ). -1 / 2 The strength should theoretically increase from 0.88 to 0.93, but the actual strength decreases instead. This is because the axial tensile stress on the ETPU foam wall increases simultaneously with the increase in draw ratio. When λ=5.5, the aspect ratio of the ETPU cells increases, and some cell walls undergo irreversible plastic deformation, forming microcracks, which weakens the load-bearing capacity of the composite monofilament. The resilience increases with the increase in draw ratio because a higher draw ratio increases the axial orientation of the TPU hard segments, resulting in a denser hydrogen bond physical cross-linking network and enhanced retraction driving force.
[0092] 4. Effect of Compatible Toughening Agent Dosage on Interfacial Bonding and Performance. A comparison of Example 5 (3 parts KG-108) and Example 1 (5 parts KG-108) shows that when the toughening agent dosage was reduced from 5 parts to 3 parts, the springback rate decreased from 68% to 63% (a decrease of 5 percentage points), the fracture strength increased from 3.5 to 3.8 cN / dtex (an increase of 8.6%), and the MFI increased from 11.5 to 16.3 g / 10min (an increase of 42%). The increase in fracture strength is due to the fact that the toughening agent KG-108, as a low-modulus elastomer (modulus of approximately 4 MPa, lower than the approximately 20 MPa of the TPU matrix), has lower inherent strength than TPU. Under stress, it preferentially deforms, forming stress concentration points. Reducing the toughening agent dosage makes stress transfer in the matrix more direct and effective. The decrease in rebound rate is due to a reduction in the number of chemically bonded interfaces between GMA groups and TPU end groups, resulting in a decrease in the interfacial bonding strength between ETPU microspheres and the TPU matrix. During the stretch-rebound cycle, partial debonding occurs at the interface, leading to relative slippage between the microspheres and the matrix, and increased viscous dissipation. A comparison between Example 6 (8 parts of KG-108) and Example 1 shows that both rebound rate and fracture strength decrease when the toughening agent is excessive. This is because excessive low-modulus toughening agent reduces the overall modulus of the matrix, and excessive GMA epoxy groups may cause slight cross-linking, significantly reducing the MFI to 8.5 g / 10 min and deteriorating processing fluidity. Therefore, 3–8 parts is a reasonable range, with 5 parts being the optimal value.
[0093] 5. Effect of heat setting temperature on resilience and internal stress. A comparison of Example 7 (heat setting temperature 100℃) and Example 1 (120℃) shows that when the heat setting temperature decreases from 120℃ to 100℃, the resilience decreases from 68% to 65% (a decrease of 3 percentage points), the elongation at break increases from 420% to 430%, and the tensile strength decreases from 3.5 cN / dtex. A heat setting temperature of 100℃ is higher than the Tg of the TPU hard segments (approximately 70–90℃), allowing the hard segment chains to gain mobility and rearrange to form a more complete physical cross-linked network. However, compared to 120℃, the mobility of the hard segment chains is lower at 100℃, the hydrogen bond reconstruction speed is slower, and the rearrangement of the cross-linked network is insufficient within the online heat setting time (approximately 2–3 seconds). Some internal stress is not completely eliminated, and the trace residual stress acts as a constraint in subsequent resilience tests, limiting the free retraction of the soft segment chains and leading to a decrease in resilience.
[0094] 6. Effect of spinning temperature on melt flowability and cell protection. A comparison between Example 8 (maximum spinning temperature 205℃) and Example 1 (200℃) shows that when the spinning temperature increases from 200℃ to 205℃, the resilience decreases slightly from 68% to 66%, the breaking strength decreases from 3.5 to 3.2 cN / dtex (a decrease of 8.6%), and the MFI increases from 11.5 to 13.5 g / 10min. At 205℃, the TPU melt viscosity decreases and flowability improves, but the higher temperature further increases the internal gas pressure of the ETPU (p2 = 1.0 × 478 / 298 = 1.60 MPa, slightly higher than the 1.59 MPa at 200℃). Simultaneously, the creep strength of the cell walls further decreases at higher temperatures, and a small number of cells undergo non-destructive deformation, resulting in a slight decrease in resilience and strength. However, 205℃ is still far below the conventional TPU processing temperature (220–240℃), and the cell integrity rate remains at 93%.
[0095] 7. Comparison of Comparative Example 1 (without gas impregnation pretreatment) and Example 1. Comparative Example 1 was not subjected to S1 gas impregnation pretreatment, but all other conditions were the same as in Example 1. The resilience rate dropped sharply from 68% to 43% (a decrease of 25 percentage points), the breaking strength decreased from 3.5 to 1.8 cN / dtex (a decrease of 49%), and the density increased from 0.85 to 1.02 g / cm³. 3 (Weight reduction effect decreased by 65%), diameter CV value increased from 2.5% to 8.5% (uniformity severely deteriorated), and breakage rate increased from no more than 1 time / h to more than 15 times / h (unable to achieve stable production). Optical microscopy showed that the internal pore structure of ETPU microspheres completely disappeared, replaced by irregular macroscopic voids (pore size 100-300μm), and the original ETPU position appeared as a hollow collapsed shell.
[0096] The thermodynamic mechanism is as follows: the initial gas partial pressure inside the pores of untreated ETPU microspheres is atmospheric pressure (0.1 MPa). When the temperature rises to 200℃ after entering the twin-screw extruder, the pressure inside the pores is p2 = 0.1 × 473 / 298 = 0.159 MPa. The external environmental pressure includes the melt static pressure in the screw mixing section (approximately 1–3 MPa) and the local high-pressure zone at the reverse screw element (up to 5 MPa). The internal and external pressure difference Δp ≈ 3–5 MPa, and the tensile stress σ on the pore wall... h=Δp·r / (2t)≈25~40MPa, far exceeding the creep strength of TPU at 200℃ (approximately 5~10MPa), therefore the cell walls fracture within seconds of entering the melting zone. After cell rupture, ETPU loses its closed-cell structure, along with its low density and high resilience; the escape of gas after rupture forms macroscopic bubbles, disrupting melt homogeneity and causing a sharp increase in spinning breakage rate; fragments from ruptured cells form defects in the TPU matrix, significantly weakening the fracture strength. This comparison directly proves that gas impregnation pretreatment is a necessary means to protect the ETPU cell structure and achieve stable spinning.
[0097] 8. Comparison of Comparative Example 2 (Conventional High-Temperature Processing) with Example 1. Comparative Example 2 used conventional TPU processing temperatures (twin-screw maximum 220°C, spinning temperature 215°C), with the rest the same as Example 1 (including gas impregnation pretreatment). The springback rate decreased from 68% to 55% (a reduction of 13 percentage points), the breaking strength decreased from 3.5 to 3.2 cN / dtex, the MFI increased from 11.5 to 14.6 g / 10 min, and the breakage rate increased from no more than 1 time / h to 6 times / h. Optical microscopy revealed that the ETPU cells were partially collapsed, with approximately 35% of the cells ruptured or merged, and the cell size distribution was extremely wide (20–200 μm).
[0098] Even after gas impregnation pretreatment (initial pressure inside the cells 1.0 MPa), at a high temperature of 220°C, the gas pressure inside the cells rises to p2 = 1.0 × 493 / 298 = 1.65 MPa, the external pressure is approximately 2–5 MPa, the pressure difference is approximately 1.0–3.4 MPa, and the tensile stress on the cell walls is approximately 10–30 MPa, still exceeding the high-temperature creep strength of TPU. More seriously, 220°C is close to or exceeds the melting temperature of the TPU hard segments (approximately 200–220°C). At this temperature, a large amount of the physical cross-linking network of the hard segments dissociates, the matrix modulus drops sharply, and the supporting capacity of the cell walls is almost lost. Furthermore, at high temperatures, the movement of TPU molecular chains intensifies, and the gas inside the ETPU can more easily escape through thermal permeation from the cell walls (the diffusion coefficient at 220°C is approximately 20 times that at 50°C), further accelerating cell collapse. This comparison indicates that, in conjunction with gas impregnation pretreatment, the processing temperature must be simultaneously reduced to below 205°C.
[0099] 9. Comparison of Comparative Example 3 (without compatibility toughening agent) and Example 1. Comparative Example 3 did not contain KG-108 toughening agent, but was otherwise the same as Example 1. The springback rate decreased from 68% to 51% (a decrease of 17 percentage points), the tensile strength decreased from 3.5 to 2.5 cN / dtex (a decrease of 29%), the MFI increased from 11.5 to 18.5 g / 10 min (an increase of 61%), and the breakage rate increased from no more than 1 time / h to 4 times / h. Without the toughening agent, the ETPU microsphere surface and the TPU matrix were bonded only by physical contact and van der Waals forces, with an interfacial shear strength of approximately 1–2 MPa, far lower than the cohesive strength of the TPU matrix of approximately 10–15 MPa. Significant shear stress is generated at the interface during the stretching process. When this stress exceeds the interfacial strength, debonding occurs, forming micron-sized voids. These voids become stress concentration sources in subsequent stretch-retraction cycles, reducing the fracture strength on one hand and increasing viscous dissipation on the other, causing the resilience rate to drop sharply to 51%, only 9 percentage points higher than pure TPU (42%). The GMA group of KG-108 reacts with the terminal hydroxyl groups of TPU to form covalent bonds, increasing the interfacial shear strength to approximately 6–8 MPa (an increase of 300%–400%), ensuring that the interface remains intact even when the matrix undergoes large deformation.
[0100] 10. Comparison of Comparative Example 4 (pure TPU monofilament) and Example 1. Comparative Example 4 was pure TPU monofilament (without ETPU and toughening agent), processed at 220°C. Resilience was 42%, and density was 1.15 g / cm³. 3 The tensile strength is 3.2 cN / dtex, and the elongation at break is 510%. Compared with Example 1, the composite monofilament of the present invention, while maintaining a tensile strength comparable to that of pure TPU monofilament, increases the resilience from 42% to 68% (+62%), and decreases the density from 1.15 g / cm³ to 0.85 g / cm³. 3 (-26%). According to the classic composite material performance prediction model, the theoretical linear superposition value of the rebound rate is 0.7×42%+0.3×68%≈49.8%, while the measured value of this invention is 68%, which exceeds the theoretical value by 18.2 percentage points (relatively exceeding by 36.5%). This superposition effect strongly proves that there is a significant time-series synergistic effect between the entropy elastic shrinkage of the TPU matrix and the expansion and energy release of the compressed gas in the ETPU cells.
[0101] 11. Comparison of Comparative Example 5 (impregnation pressure too low) with Example 1. In Comparative Example 5, the impregnation pressure was reduced to 0.2 MPa (below the lower limit of the protection range of 0.5 MPa), while the rest remained the same as in Example 1. The resilience decreased from 68% to 47%, the breaking strength decreased from 3.5 to 1.9 cN / dtex, and the density increased from 0.85 to 0.98 g / cm³. 3The cell integrity rate decreased from 95% to 15%, and the breakage rate increased from no more than 1 time / h to more than 12 times / h. When the impregnation pressure was too low, the back pressure established in the cells was insufficient (0.2MPa only increased to 0.32MPa at 200℃), which was far lower than the external melt static pressure. As a result, the cell walls underwent large-scale buckling and collapse after entering the molten section, and the result was similar to that of Comparative Example 1 (without pretreatment).
[0102] 12. Comparison of Comparative Example 6 (excessive draw ratio) and Example 1. Comparative Example 6 increased the draw ratio to 7.5 times (above the upper limit of the protection range of 6.5 times), while remaining the same as Example 1. The springback decreased from 68% to 55%, the breaking strength increased from 3.5 to 3.7 cN / dtex (a slight improvement), and the elongation at break decreased from 420% to 340%. When the draw ratio was excessive, the TPU molecular chains were overstretched, some hydrogen bonds broke irreversibly, the hard segment physical cross-linking network was stretched too tightly (overstretching), entropic elasticity decreased, the retraction driving force weakened, and the springback decreased significantly. Although further increasing the molecular chain orientation slightly increased the strength, the degradation of the springback performance was unacceptable. This comparison indicates that the upper limit of the draw ratio should be controlled within 6.5 times.
[0103] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. The high-elasticity TPU / ETPU composite monofilament according to claim 1, comprising a continuous TPU matrix and ETPU foamed microspheres dispersed therein, characterized in that, By weight, the raw material composition includes: 50-80 parts TPU resin, 20-40 parts ETPU foamed microspheres, 3-8 parts compatibility toughening agent, 0.5-2 parts antioxidant, 0.5-1.5 parts lubricant, and 0.5-2 parts nucleating agent.
2. The high-elasticity TPU / ETPU composite monofilament according to claim 1, characterized in that, The TPU resin is a polyether-type thermoplastic polyurethane or a polyester-type thermoplastic polyurethane, with a Shore A hardness of 85–95 A; the average particle size of the ETPU foamed microspheres is 2–5 mm, and the bulk density is 0.15–0.35 g / cm³. 3 The foaming ratio is 5 to 15 times, and the closed-cell rate is ≥92%.
3. The high-elasticity TPU / ETPU composite monofilament according to claim 1, characterized in that, The compatibility toughening agent is a terpolymer of ethylene-methyl acrylate-glycidyl methacrylate, wherein the content of glycidyl methacrylate is 6% to 8%; the antioxidant is a compound of hindered phenolic antioxidant 1010 and phosphite antioxidant 168 in a mass ratio of 1:1; the lubricant is stearamide or pentaerythritol stearate; the nucleating agent is nano-talc or nano-silica with an average particle size ≤100nm.
4. The preparation process of the high-elasticity TPU / ETPU composite monofilament according to any one of claims 1 to 3, characterized in that, Includes the following steps: Step 1: Place the ETPU foamed microspheres in a sealed impregnation vessel, evacuate to an absolute pressure of 5-15 kPa and maintain for 30-60 minutes, then inject high-pressure gas to a pressure of 0.5-1.5 MPa, maintain the pressure at 40-60℃ for 1.0-2.5 hours, release the pressure and discharge the material to obtain ETPU microspheres pretreated by gas impregnation. Step 2: Weigh out the TPU resin, the ETPU foamed microspheres treated in Step 1, the compatibility toughening agent, the antioxidant, the lubricant, and the nucleating agent according to the formula, and put them into a high-speed mixer. Mix for 10 to 25 minutes at a temperature ≤50℃ and a speed of 100 to 300 rpm to obtain the premix. Step 3: Feed the premixed material into a co-rotating twin-screw extruder and melt-blend it under the conditions of length-to-diameter ratio of 44:1 to 52:1 and screw speed of 200 to 350 rpm. The extrudate is then cooled with water, pelletized, and dried to obtain composite masterbatch. Step 4: After drying the composite masterbatch, it is fed into a single-screw spinning extruder for melt spinning. The melt is extruded through the spinneret to form a melt stream. After cooling and oiling, it is drawn, heat-set and wound to obtain the nascent composite monofilament. Step 5: Heat-treat the nascent composite monofilament at 80-110℃ for 2-6 hours, and then cool it to room temperature at a rate of 0.5-1.0℃ / min to obtain the final product.
5. The preparation process according to claim 4, characterized in that, The high-pressure gas mentioned in step one is nitrogen or carbon dioxide with a purity of ≥99.5%.
6. The preparation process according to claim 4, characterized in that, The mixing section of the co-rotating twin-screw extruder described in step three uses a combination of toothed discs and reverse threaded elements, with a shear stress ≤30kPa.
7. The preparation process according to claim 4, characterized in that, In step three, the temperatures of the heating zones of the extruder are as follows: Zone 1 135-145℃, Zone 2 155-165℃, Zone 3 170-180℃, Zone 4 175-185℃, Zone 5 180-190℃, Zone 6 185-195℃, Zone 7 190-200℃, and Zone 8 195-205℃. The exhaust section maintains an absolute pressure of 20-40 kPa for vacuum exhaust.
8. The preparation process according to claim 4, characterized in that, In step four, the spinneret has 30 to 120 holes with a diameter of 0.3 to 1.2 mm and an aspect ratio of 2 to 4. The first-stage hot drawing is carried out using a water bath or hot roller heating method, and the second-stage hot setting is carried out using a hot roller heating method.
9. The preparation process according to claim 4, characterized in that, The specific steps of step four are as follows: After drying, the composite masterbatch is fed into a single-screw spinning extruder for melt spinning. The barrel temperature is successively 160-165℃, 175-180℃, 190-195℃, and 195-200℃, and the die head temperature is 195-205℃. The melt is extruded through the spinneret to form a melt stream. After cooling and oiling, it undergoes primary hot drawing at a drawing temperature of 50-80℃ with a draw ratio of 3.5-6.5 times. Subsequently, it undergoes secondary heat setting at 100-130℃ with a heat setting ratio of 0.95-1.0 times and a winding speed of 200-600m / min to obtain nascent composite monofilament.
10. The preparation process according to claim 4, characterized in that, The cooling process in step four involves passing the molten stream through an air gap and then entering a water bath or cooling box at 15–30°C for cooling and solidification. The oiling process uses a mineral oil-based emulsion containing antistatic agents and cohesive agents, with an oiling rate of 0.8%–1.5%.
